The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1590/fst.03519
|View full text |Cite
|
Sign up to set email alerts
|

Consumer behavior of organic and functional foods in Brazil

Abstract: The objective of this study was to correlate the gender and behavior of consumers of organic foods enriched with functional properties. The study was carried out by investigating the profile of organic and functional food consumers through the application of a questionnaire. A total of 1230 responses (of the questionnaire) were collected from people from all Brazilian states through social networks and e-mails following the snowball technique during the months of February and March 2017. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 29 publications
3
11
1
2
Order By: Relevance
“…This agrees with previous studies reporting that acceptability of functional foods varies with gender in Uruguay (Ares & Gámbaro, 2007). Martins et al, 2020 showed that women expressed greater interest in consuming organic foods enriched with functional properties compared to men in Brazil. It is widely reported women are more interested in eating healthily than men (Gök et al, 2019).…”
Section: Impact Of Time On the Interest Of New Products With Different Nutritional Benefitssupporting
confidence: 93%
“…This agrees with previous studies reporting that acceptability of functional foods varies with gender in Uruguay (Ares & Gámbaro, 2007). Martins et al, 2020 showed that women expressed greater interest in consuming organic foods enriched with functional properties compared to men in Brazil. It is widely reported women are more interested in eating healthily than men (Gök et al, 2019).…”
Section: Impact Of Time On the Interest Of New Products With Different Nutritional Benefitssupporting
confidence: 93%
“…This perception is consistent with the results of a study conducted with adult consumers in Switzerland, which showed that using the label “fruit sugar” instead of “sugar” in packaged foods increased participants' perceived healthiness of the foods ( 30 ). Regarding the production type, a study analyzing adult consumers' perception of organic foods in Brazil showed that these products are perceived as healthier than the conventional and as they can improve the quality of life of the consumers ( 31 ). Other study conducted with Brazilian university students showed that food healthiness was associated with being natural and containing low amounts of additives ( 32 ), which can explain why the participants in our study valued organic sugar.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, organic foods consumption may reduce overweight, obesity, and the risk of allergic disease ( Essoussi and Zahaf, 2008 ). In the same study by Martins et al (2020) , an increased consumers’ motivation of organic foods consumption was related to the awareness that organic foods are healthier and can improve quality of life.…”
Section: Benefits and Future Prospectsmentioning
confidence: 92%
“…A study among 274 Brazilian organic foods consumers, conducted by de Morais Watanabe, Alfinito, Curvelo and Hamza (2020) , they indicated that functional and emotional values positively affect consumers' trust and that only emotional value motivates purchase intention. Whereas in another study, which investigates gender-based behavioural pattern of GSO foods, women expressed greater interest in consuming fruits and vegetables mostly compared to men; and while both men and women agree that organic foods are produced in a sustainable manner, their high price, difficult access, irregular supply and availability in few establishments were highlighted as the main limiting factors for not consuming organic foods ( Martins et al, 2020 ). A similar study conducted in Spain and Thailand towards consumers' perception and attitude, as well as retailers’ attitude to GSO foods showed similar results, respectively, with cost being a premium factor ( Rodríguez-Bermúdez et al, 2020 ; Kantamaturapoj and Marshall, 2020 ).…”
Section: Challenges Associated With Gso Foodsmentioning
confidence: 99%